Depressed lymphocyte transformation by yersinia and Escherichia coli in yersinia arthritis. Issue 2 (April 1983) - Leino, R; Vuento, R; Koskimies, S; Viander, M; Toivanen, A
Abstract : Lymphocyte transformation responses were studied in 21 patients with acute yersinia infection followed-up after the acute infection for up to one year. Eight patients had reactive arthritis caused by yersinia. The responses to the causative serotype of yersinia were significantly lower (p less than 0.05) in patients with arthritis than in those without arthritis. Stimulation with Escherichia coli gave lower responses than with yersinia, but with E. coli the difference between arthritic and nonarthritic groups was more significant (p less than 0.02). The responses to yersinia and E. coli were not correlated with the presence of HLA B27. Lymphocyte transformation by purified protein derivative of tuberculin, streptokinase-streptodornase, phytohaemagglutinin, or concanavalin-A revealed no significant differences between the arthritic and nonarthritic groups. The role of the enterobacterial common antigen in the pathogenesis of reactive arthritis and ankylosing spondylitis is discussed.